Septic abortion as a cause of maternal morbidity and mortality. - Chumbe, Ovidio (2015)
The authors study maternal morbidity and mortality in 1088 cases of septic abortion attended at the Maria Auxiliadora Hospital’s Department of Obstetrics and Gynecology, from January 1.º, 1990 through December 31, 1993. Findings were compared with those before 1990. Abortion rate in our Hospital is 299 per 1000 live newborns and septic abortion rate 18%. Endometritis complicated all the cases and other severe complications were found in 14,4% of cases. Septic abortion today is more frequent in adolescents than before 1990 and tends to ocurr earlier in pregnancy. Ten percent of patients were submitted to abdominal hysterectomy with or without adnexectomy. maternal mortality by septic abortion was 603 per 100000 live newborns. In conclusion, septic abortion is an important cause of maternal morbidity and mortality in our hospital and its frequency tends to increase.